Early COVID-19 School Policies' Impact on Families and Youth Engagement in Virtual Learning and Telemental Health. - Domlyn, Ariel M; Collier, Tristan; Chehoski, Brooke E; Haines, Christopher; Patterson, Brittany; Stevens, Robert; Niles, Madison L; Weist, Mark D (Children & Schools, 2024)
The COVID-19 pandemic quickly and significantly impacted students, schools, and communities. As part of a larger multisite study, the present investigation aimed to understand the effect of the pandemic-related switch to virtual schooling and virtual mental health services on youth. Specifically, this study aimed to explore the impacts of the pandemic on school administrators and staff, students, and families invested in supporting youth mental health. Focus groups were held in two disparate communities within the United States. Participants were members of two school mental health coalitions acting as key informants and included mental health program directors, school clinicians, parents of students, and community leaders. Data were analyzed using iterative rapid qualitative analysis. Salient themes include the role of family characteristics, communication, and infrastructure on use of virtual learning and virtual mental health services. Study findings indicate that fostering trust and increasing communication between school districts and families may ameliorate challenging policy transitions in future crises.